Persepsi Karyawan Terhadap Pengaruh Peran Auditor Internal, Keadilan Organisasi dan Pengendalian Internal Terhadap Pencegahan Kecurangan (Fraud) (Studi Empiris pada Beberapa Perusahaan Perbankan di Jakarta) - Mohammad, Yamin; Chandra, Syah Putri (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2025)
The aims of this research is for knowing about employees perception to the role of internal auditor, organizational justice and internal control for fraud preventif. The responded for this research is theemployee who working in banking companies in Jakarta. For the sample, There are have 74 employees from7 banking companies. The research used is quantitative method and for the analysis method used isdesciptive statistics, data quality test, classic assumption test and hypothesis test. The result showed that therole of organizational justice had no effect for fraud prevention. the internal auditor and internal control hada significant effect for fraud prevention. And the result for simultan test is the role of internal auditor,organizational justice and internal control had effect for fraud prevention. Keywords: Internal auditor, organizational justice, internal control fraud